Strategi Perusahaan Halodoc dalam Meningkatkan Sistem Digitalisasi Bisnis Layanan Jasa Kesehatan di Indonesia - Erwin Permana; Claradhika Putri; Elsa Amanah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Along with strengthening the digital ecosystem in Indonesia, digitalization is occurring at all levels. Health services that were previously monopolized by hospitals are now starting to emerge with digital hospitals without the limitations of walls. This of course provides broad benefits for society and is interesting to research. One of the popular digital service companies in Indonesia is Halodoc. This research aims to analyze the halodoc company strategy in improving the digitalization system of the health services business in Indonesia. The research was conducted using a descriptive qualitative approach. Research data comes from various credible popular sites and official publications. The research results reveal that the strategies implemented by Halodoc in improving the digitalization system of the health services business in Indonesia include, 1. Halodoc improves the quality of electronic services in the halodoc application, such as in terms of the availability of information that makes it easier for users, increasing the privacy or security of user accounts, graphic style , and reliability. 2. Carrying out marketing techniques in the form of omnichannel marketing, especially unification of channels used by consumers such as Facebook, Twitter, YouTube, TikTok, and also Instagram chat, both via audio and video calls. 3. Halodoc maintains positive sentiment from users so that users feel satisfied with the services provided. 4. Increase E-Health literacy, because someone with high E-Health literacy tends to have a higher intention to use services in the Halodoc application. 5. The Halodoc application provides doctors who are reliable and experienced in handling patient complaints. 6. Halodoc leverages data for personalized user experiences. This research suggests improving the medicine delivery system which can be done by improving the ordering system, improving the quality of the packages and packaging of the medicines.